2020
DOI: 10.1093/heapol/czaa008
|View full text |Cite
|
Sign up to set email alerts
|

Do you need to pay for quality care? Associations between bribes and out-of-pocket expenditures on quality of care during childbirth in India

Abstract: Abstract While it is mandated that reproductive and child health services be provided for free at public facilities in India, qualitative evidence suggests it is common for facilities to request bribes and other informal payments for medicines, medical tests or equipment. This article examines the prevalence of bribe requests, total out-of-pocket expenditures (OOPEs) and associations between bribe requests and total OOPEs on the experience of quality of care and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 27 publications
0
17
0
Order By: Relevance
“…Even small costs may deter women from receiving quality care, decrease person‐centered care, and potentially add barriers for women to access healthcare facilities in the future either for herself or her newborn. 10 Reporting a required payment for PPE during labor/delivery and postnatal visits was associated with PPD; however, in models where all economic indicators were included in the model, only paying for PPE during postnatal visits was associated with PPD. One potential explanation for this association may lie in the fact that postnatal visits are typically completely free, in contrast to deliveries, which often require purchase of extraneous items (razor, cotton wool, etc); thus, PPE during labor/delivery represented an expected, and therefore acceptable, cost.…”
Section: Discussionmentioning
confidence: 93%
“…Even small costs may deter women from receiving quality care, decrease person‐centered care, and potentially add barriers for women to access healthcare facilities in the future either for herself or her newborn. 10 Reporting a required payment for PPE during labor/delivery and postnatal visits was associated with PPD; however, in models where all economic indicators were included in the model, only paying for PPE during postnatal visits was associated with PPD. One potential explanation for this association may lie in the fact that postnatal visits are typically completely free, in contrast to deliveries, which often require purchase of extraneous items (razor, cotton wool, etc); thus, PPE during labor/delivery represented an expected, and therefore acceptable, cost.…”
Section: Discussionmentioning
confidence: 93%
“…Our own past research has shown that as providers become overworked and service volumes increase, better clinical care is often at odds with better, more personal, care [30]. Provider stress, and facility management, were shown to be critical contextual pre-conditions for being open to improvement, and anecdotally reported by research teams for this study as well [31]. In this context, our findings are particularly important.…”
Section: Resultsmentioning
confidence: 51%
“…Studies on drivers of poor PCMC suggest providers treat women differently based on women's appearance, assumptions of women's expectations and level of understanding, and women's ability to advocate for themselves (Afulani et al, 2020a,b;Smith et al, 2020). Others have highlighted the role of women's ability to pay for services including bribes (Warren et al, 2017;Landrian et al, 2020). However, understanding disparities was not the primary goal of these studies, and its drivers were not explored in detail.…”
Section: Introductionmentioning
confidence: 99%